Nilai-Nilai Dakwah Dalam Syair Saman Gayo - Maini Sartika; Desi Purnama Sari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This research is entitled “Preaching Value in Saman Gayo Poems” purposed to figure out any kind of preaching value contained in Saman Gayo poems. The researsch used qualitative method and the data are descriptive with documentation and interview approach. The theory used in this reasearch was Hermunistic Theory, in which the interpretation is explained. This theory refers to interpreting a word or a sentence which is difficult to be understood in different languages and the meaning of difficult figurative words. The data analysis method used in this research is on-field analysis, Miles dan Huberman model. This method consists of analyzing the data; data reduction, data presentation, and conclusion. Based on the result, it can be concluded that some preaching values found in Saman Gayo poems as “Ku ini nge sawah hana de salamku, Ini nge mudemu mat jarike mule kite, kite bermat jari”. Meaning: Here has arrived, what my greetings, This has met our greetings first, we shake hands. The poem explains that the meaning of greetings contains respect in accordance with the concept of Islam.